Maltese in London, 1966-1969: attitudes to Maltese in London, 1969 - Dench, Geoff (UK Data Service, 1976)
The purpose of this survey was to investigate non-Maltese peoples' contacts with and knowledge of Maltese living in London, to provide some estimates of the general distribution of the attitudes towards Maltese and the Maltese community. The main items on which information was sought were the extent of respondents' contact with Maltese people, their knowledge and acceptance of the Maltese `bad name', their judgment on whether or not it should be regarded as a collectively responsible group.